Global Ultra-models in Active Disturbance Rejection Control of Nonlinear Differentially Flat Systems - H. Sira Ramírez (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2015)
Global ultra-models are introduced as a paradigm for vastly simplifying the design of observer-based linear output feedback control laws in output trajectory tracking problems for a large class of uncertain nonlinear flat systems. An ultra-model simply lumps, as an unknown time-varying disturbance, the combined effects of all uncertain state-dependent (i.e., endogenous) nonlinearities as well as those of external (i.e., exogenous) perturbation inputs present in the input-to-flat output model of the system. As a result, a global ultra-model based controller design only requires knowledge of the system order and of the nonlinear control input gain function. An extended high gain observer based control scheme is proposed for linear Active Disturbance Rejection (ADRC) for nonlinear differentially flat systems. An Illustrative case study example is presented.